Fenomena Representasi Visual Identitas Fesyen Dangdut di Media Sosial: Analisis Instagram @isdadahlia dan @cadburylemonade - Salsa Alfina Zhahra; Ririn Puspita Tutiasri (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2026)
This research discusses the visual representation of dangdut fashion identity through an analysis of Instagram posts by @isdadahlia and @cadburylemonade. Social media, especially Instagram, plays an important role in the formation of visual identity in the digital era, including in the realm of popular culture such as dangdut music. In this context, fashion is not only an aesthetic element, but also a means of visual communication that contains messages of identity, social class and cultural expression. This research uses a descriptive qualitative approach with Roland Barthes' semiotic analysis method to reveal three layers of meaning: denotative, connotative and myth. The results showed that @isdadahlia's account displayed glamorous, elegant and professional dangdut fashion, reinforcing her image as a senior singer with authority in the entertainment industry. In contrast, @cadburylemonade presented an experimental, theatrical and pop culture-influenced style that represented freedom of expression and inclusivity in fashion. This comparison shows a shift in meaning in dangdut fashion, from an established symbol of professional identity to a fluid and dynamic form of self-expression. Visual symbols shared on social media formed a new myth that influenced the way the public understood identity construction, cultural values and self-image today. This finding confirms that the representation of dangdut fashion on social media is also a sociocultural narrative that continues to be.